Indigofera suffruticosa Mill as new source of healing agent: Involvement of prostaglandin and mucus and heat shock proteins - Luiz-Ferreira, Anderson; Cola, Maira; Barbastefano, Victor; Farias-Silva, Elisangela; Calvo, Tamara Regina [UNESP]; Albino de Almeida, Ana Beatriz; Pellizzon, Claudia Helena [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP]; Vilegas, Wagner [UNESP]; Monteiro Souza-Brito, Alba Regina (Elsevier B.V., 2011)
Ethnopharmacological relevance: Indigofera suffruticosa is specie typical of the Cerrado or Brazilian savannah; it is a member of the Fabaceae family - in folkmedicine is used for gastric disorders, infection and inflammation.Aim of the study: Ethyl acetate fraction (AcF) and aqueous fraction (AqF) of the methanolic extract of I. suffruticosa leaves were evaluated against acute gastric ulcer. The AcF fraction was selected to assess its activity in ulcer healing and its gastroprotective effects via mucus and gastric secretion.Materials and methods: The gastroprotective action of AcF and AqF fractions were evaluated in a rodent experimental model. The action mechanisms, involvements of the antisecretory action, mucus and prostaglandin production, toxicological and healing activity of the AcF (100 mg/kg, p.o.) were evaluated. We also used histological analysis (HE and PAS) and immunohistochemical (PCNA and HSP-70) assays to evaluate the effects of I. suffruticosa.Results: AcF significantly inhibited the gastric mucosal damage caused by ethanol. This effect was statistically significant in 100 mg/kg group compared vehicle. AcF did not interfered with gastric secretion, significantly increased the PGE(2) and mucus production (validated in PAS technique). The gastroprotection was attenuated by pretreatment with N-ethylmaleimide, but not L-NAME. In acid-acetic-induced ulcer model AcF accelerated ulcer healing. Immunohistochemistry analysis showed induction of proliferating cell (PCNA) and heat shock protein (HSP 70).Conclusions: These results showed that AcF acted as gastroprotective agent stimulating prostaglandin, mucus and HSP70. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Antiulcerogenic activity; Indigofera suffruticosa; Gastroprotection; Heat shock protein